Influence of Variable Permeability and Radiation Absorption on Heat and Mass Transfer in MHD Micropolar Flow over a Vertical Moving Porous Plate. (18th February 2013) - Harish Babu, D.; Satya Narayana, P. V.
Abstract : An analysis of unsteady free convection with heat and mass transfer flow for a micropolar fluid through a porous medium with a variable permeability bounded by a semi-infinite vertical plate in the presence of heat generation, thermal radiation, first-order chemical reaction, and the radiation absorption is reported. The plate is assumed to move with a constant velocity in the direction of fluid flow. A uniform magnetic field acts perpendicular to the porous surface which absorbs micropolar fluid with a suction velocity varying with time. The dimensionless governing equations for this investigation are solved analytically using two-term harmonic and nonharmonic functions. To observe physical insight and interesting aspects of the problem, the velocity, angular velocity, temperature, and concentration field are numerically studied and displayed graphically for pertinent parameters.